Taxation of Temporary Jobs: Good Intentions with Bad Outcomes? - Pierre Cahuc; Olivier Charlot; Franck Malherbet; Helène Benghalem; Emeline Limon (Institute for the Study of Labor (IZA), 2016)
This paper analyzes the consequences of the taxation of temporary jobs recently introduced in several European countries to induce firms to create more open-ended contracts and to increase the duration of jobs. The estimation of a job search and matching model on French data shows that the taxation of temporary jobs does not reach its objectives: it reduces the mean duration of jobs and decreases job creation, employment and welfare of unemployed workers. We find that a reform introducing an open-ended contract without layout costs for separations occurring at short tenure would have opposite effects.
Keywords: J63; J64; J68; 330; temporary jobs; employment protection legislation; taxation